Hemorrhagic Syndrome in Dogs Induced by Intravenous Thrombin - Girolami, A; Cliffton, E. E; Agostino, D (Thrombosis and Haemostasis, 1966)
The intravenous administration of thrombin (70 N. I. H. u/kg) caused in the dog a decrease in platelets, factor V, factor VIII and fibrinogen, a prolongation of glass and silicone clotting times, prothrombin and partial thromboplastin times, decreased prothrombin consumption and defective thromboplastin generation. This resulted in a generalized bleeding syndrome. Increased fibrinolysis occurred after an initial phase of inhibition of fibrinolysis. It is suggested that this hemorrhagic syndrome is similar to some conditions observed clinically.